The Evolution of Corporate Cash. Issue 4 (14th February 2019) - Graham, John R.; Leary, Mark T.
Abstract : In a study published recently in the Review of Financial Studies, the authors examine and then attempt to explain the considerable variation in the cash‐to‐assets ratios of U.S. public companies over a nearly 100‐year period. For example, between 1920 and 1945, the average cash holdings of both small and large U.S. companies tripled. By 1970, however, the cash levels of both had fallen back to their starting point in the early 1920s. Then, at the start of the 1980s, the cash policies of small and large companies began to part ways. Thanks to the very large cash holdings of the wave of companies that went public during the next two decades, the average corporate cash ratio increased sharply from 1980 to 2000—a period when the cash holdings of large, established U.S. companies remained largely unchanged. But since 2000, it has been the large U.S. companies—many of them multinationals with profits "trapped" overseas—that have experienced the largest increase in cash holdings. The authors find especially compelling evidence that the significant increase in average cash holdings from 1980 to 2000 was driven primarily by a "Nasdaq effect" in which a large number of firms went public on the Nasdaq while holding amounts of cash that increased steadily throughout this 20‐year period. This Nasdaq effect was most pronounced among unprofitable, largely debt‐free, high‐growth, and high‐volatility firms, most of which operated in the healthcare or high‐tech industries. And this trend may well continue in the future, given recent reports of a growing fraction of IPOs by companies that have yet to show profits. But along with and apart from this "Nasdaq" effect, the authors also find that for NYSE companies, the sensitivities of company‐specific cash holdings to commonly studied variables have been remarkably stable during the past 90 years. The kinds of companies that have operated with high cash‐to‐assets ratios in recent years—riskier companies with growth opportunities and little if any profits or use of debt—have had large cash holdings in nearly every decade during the last century. And as in the past, relatively low‐growth and low‐risk public companies producing steady income have continued to operate with lower levels of cash. But even with this relative stability of firm‐specific cash sensitivities, the authors do not find changes in corporate characteristics helpful in explaining the changes in aggregate cash holdings over time, particularly the large increases during the 1930s and early '1940s, and the period since 2000. The largest roles in such increases appear to have been played by macroeconomic factors, such as the level of general economic growth and its effect on corporate profitability and investment. Nevertheless, in recent times, even after taking these macro and micro factors into account, the authors' study provides clear evidence that the repatriation tax incentives (that were recently eliminated by the 2018 tax legislation) have played the largest role in the increase in aggregate corporate cash holdings that has taken place since 2000. With the recent elimination of such incentives, the cash holdings of large multinationals are likely to fall toward pre‐2000 levels.